The Relationship Between Working Duration and Forward Head Posture - Karang, Ni Nyoman Melani; Kadek Dwi Pradnya Lestari (International Journal of Public Health Excellence (IJPHE), 2023)
Forward head posture refers to the anatomical alignment of the head positioned anteriorly to the shoulders. An imbalance in the muscles of the cervical region characterizes this disorder. This phenomenon can be attributed to multiple variables, one of which pertains to the length of the work period. This investigation seeks to establish the relationship between working duration and forward head posture. This research method uses a cross-sectional analytic observational study design that was carried out from February to March 2023 in Gianyar. The study employed a sample size of 60 individuals, selected by the utilisation of a basic random sampling methodology. The CVA measurement uses the MB Ruler, and the duration of work is measured with a self-report questionnaire. Data analysis in this study used the SPSS version 24 application with bivariate tests using Chi Square and Spearman's rank tests. The findings of this study revealed a statistically significant association between work duration and forward head posture, as indicated by a p-value of 0.012 (p < 0.05). The findings of this study indicate a statistically significant correlation between the duration of employment and the occurrence of forward head posture.